Analysis of Design for Assembly (DFA) in Waste Separation Machine of Ferromagnetic and Non-Ferromagnetic Material - Arief, Dodi Sofyan; Ilyandi, Rifki; Abidin, Tekad Indra Pradana; Hamzah, Amir (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
Design for Assembly (DFA) is one of method in the assembly systems to ease the assembly during simultaneous process from the beginning until become new products of the whole components. However, the obstacles in assembly process could be occurred in waste separation machine. Therefore, in order to obtain the optimization of assembly process, it is needed to conduct an analysis of component design before the production. DFA analysis will obtain the value of assembly efficiency. The efficiency value of prototype machine will achieve a way to separate the waste, both ferromagnetic and non-ferromagnetic materials. Furthermore, efficiency value theoretically on assembly of waste separation machine is 14.22% at 548.47seconds. The efficiency value of waste separation machine after assembly process in actual condition is 11.83% at 658.88seconds. The distinction efficiency value is caused by difficulties in assembly of the belt roller and sub assembly of base support on motor. As consequences, the time to get assembly will take more time on actual condition rather than theoretically.